PENERAPAN ANALISIS MULTIDIMENSIONAL SCALING UNTUK MEMETAKAN PERSEPSI STAKEHOLDERS TERHADAP MUTU LULUSAN IAIN PONTIANAK - Sumin Sumin (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2017)
All society of academicians IAIN Pontianak must supporting vision and mission of IAIN Pontianak for the sake of quality of graduates who have higher competency and international insight one of concrete effort is doing community satisfaction survey towards the quality of graduates of IAIN Pontianak as external information source, next data perceptive analyzed with appropriate statistic tool, one of application tool is Multidimentional Scaling Tests (MDS). This research using descriptive methods (descriptive research) with the intention of making emphirical description Multidimentional Scaling Application (MDS) on stakeholders perceptive to map the quality of garduates of IAIN Pontianak. Population on this research is IAIN stakeholders in Pontianak, that is community which directly connected to graduates of IAIN Pontianak, or private institution or government as graduates of IAIN Pontianak user. Sample of this research using purposive methods sampling 100 respondents. IAIN segmentative of quality variables that has negative perceptive by community is Disciplines ( X9) and Motivates (X11), IAIN segmentative variables that have positive perceptive by stakeholders are Integrity / Ethics variables and Morality ( X1), Professionalism at works (X2), Insight between disciplines (X3), Leadership( X4), Teamworks( X5), Foreign Language Ability (X6), Communication Ability ( X7), Using Information Technology (X8), Honesty (X10), Work Ethics(X12), Innovative and Creativity ( X13), Solving Problems Ability (X14). There is high competition between 3 higher education in Pontianak. Those are: IAIN, Poltekes and Polnep. As spatial IAIN Pontianak closer to UNTAN, it is also means that UNTAN is the strongest competitor of IAIN Pontianak. Key words: MDS, Perceptive Map, Graduates quality, IAIN Pontianak